Changes in the Structure of Agricultural Production in the European Union with Particular Emphasis on Poland and Latvia - Tłuczak, Agnieszka (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
Many of phenomena, their growth or trend, are dependent on the interactions between neighboring areas. Model of shift-share analysis represent a growth rate (rate of change) of the different options phenomenon by taking into account the phenomenon of increase in the neighbouring area. The aim of the study is to analyze the changes in the commodity structure of agricultural production in the European Union according to the selected types of agricultural products using of shifts share analysis. The study assesses the rate of change the size of the phenomenon and identified and estimated the share of structural, sectoral and regional (local spatial) in the size of the effect of the global (agricultural production in the European Union overall) in the EU countries.